Quarry Dust As A Fine Aggregate Replacement in Concrete Masonry Blocks for Sustainable Construction - Gopalakrishnan Nair, Deepa; V Thomas, Robert (International Journal of Sustainable Construction Engineering and Technology, 2023)
Acute shortage of raw materials and their escalating prices together with the unhealthy competition among the manufactures is adversely affecting the sustainability of concrete building blocks now a days. Depletion of natural aggregates and accumulation of construction wastes are other issues challenging the sustainability of construction. Application of quarry dust, the waste material from stone crushing industry as fine aggregate replacement in concrete has practical significance in this regard. This paper investigates the suitability of quarry dust as replacement (10% to 100%) to natural aggregate in concrete masonry blocks. Successful replacement of 30 % can be suggested for load-bearing masonry units with superior strength, comparable durability and better performance in aggressive environments. Suitability of the proposed blocks in structural masonry as well as sustainable construction was also verified.100% replacement of quarry dust was also found suitable for load bearing masonry units with comparable strength and durability characteristics.